Conditions of learning loss in students during the pandemic covid-19 - Ningsih, Lucy Febria; Ifdil, Ifdil (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
The Covid-19 pandemic that spread in Indonesia resulted in many sectors fawning including education. The government issued a policy to carry out learning activities from home to reduce the spread of co-19. Changed learning activities result in the possibility of learning loss. The method used in this research is a quantitative method with a descriptive research type. The sample in this study was 237 students at SMA N 1 Kec. Lareh Sago Halaban. The data were obtained from the results of the learning loss questionnaire which had been filled out by the students. Data were analyzed using descriptive analysis techniques with the assistance of JASP version 16.3. The results of the study revealed that learning loss in students during the Covid-19 pandemic was generally in the moderate category. Based on the findings of this study, it is expected that counseling teachers or counselors can provide assistance in the form of guidance and counseling services.